2011
DOI: 10.1007/s00595-011-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of serum p53 antibody as a tumor marker in colorectal cancer patients

Abstract: The approved kit for S-p53Ab testing was found to be an effective tumor marker of colorectal cancer. The positive rate of S-p53Ab was significantly higher in patients with cancer involvement of the lymphoid tissues. The positive rate of S-p53Ab was higher than that of CEA and CA19-9 in patients with stage I colorectal cancer, suggesting that the S-p53Ab is a useful tumor marker for patients with early-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…Previous studies (1,(4)(5)(6)8,9) reported a positive Ap53Ab expression rate of 24.0-33.1% in CRC patients. Our data were consistent with those reports in terms of the positive Ap53Ab rate.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Previous studies (1,(4)(5)(6)8,9) reported a positive Ap53Ab expression rate of 24.0-33.1% in CRC patients. Our data were consistent with those reports in terms of the positive Ap53Ab rate.…”
Section: Discussionmentioning
confidence: 90%
“…A recent report (4) demonstrated that positive Ap53Ab expression was detected in 72 (15.1%) of 478 CRC patients with stage 0 and I disease. Another study (5) reported that 9 of 38 CRC patients (23.7%) with stage I disease exhibited positive Ap53Ab expression. In our series, the positive rate of Ap53Ab expression in stage 0 and I and only stage I cases was 16.7 and 20.0%, respectively, while that of CEA in stage 0 and I and only stage I cases was 12.5 and 13.1%, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations